Design of Indicator Strip Using Polystyrene (PS) and Polymethylmethacrylate (PMMA) for Detection of Diclofenac Sodium in Traditional Pain Relief Herbal Medicines - Ibrahim Dalli; Danni Ramdhani; Aliya Nur Hasanah (Universitas Gadjah Mada, 2017)
Diclofenac sodium is one of analgesic which added to herbal medicines to enhance the effects. One of a qualitative method that is easy, efficient and simple is an indicator strip test. Indicator strip based polystyrene (PS) and polymethylmethacrylate (PMMA) was made to detect of diclofenac sodium which misused in traditional pain relief herbal medicine. Indicator strip was made by reagent blending method with specific reagents, copper sulfate (CuSO4), ferric chloride (FeCl3) and vanillin sulfate. The principle of the indicator strip in detecting diclofenac sodium is with the occurrence of a color reaction. The PS and PMMA were made in the concentration of 5, 7.5 and 10% and the mixture of PS and PMMA 1:5 and 1:6 respectively with a ratio of solvent and reactant 6:4; 7:3 and 8:2. The best indicator strip is PMMA-CuSO4 5% (7:3), PMMA-FeCl3 5% (7:3) and PMMA-Vanillin sulphate 7.5% (7:3). The detection limit of the PMMA-CuSO4 5% (7:3) was at 50 ppm, PMMA-FeCl3 5% (7:3) showed detection limit of 12,500 ppm and PMMA-vanillin sulfate 7.5% (7:3) showed detection limit of 500 ppm. All indicator strips stable up to 29 weeks. The indicator strip can be used as an alternative method to detect diclofenac sodium in herbal medicine.